Beyond microbes: Are fauna the next frontier in soil biogeochemical models?. (November 2016) - Grandy, A. Stuart; Wieder, William R.; Wickings, Kyle; Kyker-Snowman, Emily
Abstract: The explicit representation of microbial communities in soil biogeochemical models is improving their projections, promoting new interdisciplinary research, and stimulating novel theoretical developments. However, microbes are the foundation of complicated soil food webs, with highly intricate and non-linear interactions among trophic groups regulating soil biogeochemical cycles. This food web includes fauna, which influence litter decomposition and the structure and activity of the microbial community. Given the early success of microbial-explicit models, should we also consider explicitly representing faunal activity and physiology in soil biogeochemistry models? Here we explore this question, arguing that the direct effects of fauna on litter decomposition are stronger than on soil organic matter dynamics, and that fauna can have strong indirect effects on soil biogeochemical cycles by influencing microbial population dynamics, but the direction and magnitude of these effects remains too unpredictable for models used to predict global biogeochemical patterns. Given glaring gaps in our understanding of fauna-microbe interactions and how these might play out along climatic and land use gradients, we believe it remains early to explicitly represent fauna in these global-scale models. However, their incorporation into models used for conceptual exploration of food-web interactions or into ecosystem-scale models using site-specific data could provide rich theoretical breakthroughs and provide a starting point for improving model projections across scales. Highlights: Microbial communities are now explicitly represented in soil models. Fauna are implicitly but not explicitly represented in models. Microbivory influences microbes and is a promising faunal behavior to incorporate in models. Unpredictable direction and magnitude of fauna effects makes them difficult to model. Incorporation of fauna into ecosystem models could provide theoretical breakthroughs.